Analisa Qos (Quality Of Service) Jaringan Wireless Outdoor Client Kgsnet - Rivaldi, Ahmad; Edi Surya Negara; Fatoni; Suryayusra (STMIK Budi Darma, 2024)
Internet availability is absolute in the digital era like today. The need for fast information makes the internet very important, this need must be supported by the availability of internet that is always available and stable. For that, network performance must be prepared as well as possible in order to get a stable internet connection. Currently, the use of ISP or Internet Service Provider is very common in the business world because it has effective and flexible services. KGSNet is one of several ISPs available. KGSNet offers a stable and fast internet connection, unlimited internet without quota and as much as you like. Currently, some of the customers connected to KGSNet using outdoor wireless devices still experience problems with delays in data delivery and connection instability when accessing data communication services. Therefore, a study was conducted to see the performance of the KGSNet outdoor wireless client service with the Quality Of Service (QOS) method, the Reliability, Maintainability And Availabilty (RMA) method and also the Quality Of Experience (QOE) method to be able to minimize and identify network disruptions early so that the outdoor wireless client network can always be in maximum performance to support KGSNet customer service. The QOS parameters used to measure are bandwidth, throughput, delay, packet loss and jitter, which are then compared with the Telecommunications and Internet Protocol Harmonization Over Network (TIPHON) version standardization. The RMA parameters are MTTF, MTTR and MTBF. While the QOE parameters used are Round Trip Time (RTT).